Adesão de católicos ao evangelismo de prosperidade : uma análise dos motivos da mudança de denominação religiosa em São José da Coroa Grande - Ramos, Argentina Pinho Cavalcante (2012)
The aim of this paper is analyze the accession of Catholic evangelism for prosperity through the growth of Neopentecostalism in contemporary times, with reference to the city of St. Joseph Crown Grande, located in Pernambuco. Considering the increase in number of worshipers leaving the Catholic Church for the Universal Church of the Kingdom of God, it was the one that stood out, considering that this increase is related to their representation in the locality due to its role in the induction of persons, managing to attract new supporters and while keeping the faithful older. Data collection was done by means of participant observation in the locality during the 'meeting' local, semi-structured interviews and an extensive bibliography. We will try to focus on the reasons and processes relevant conversions and so accepted by the faithful who make the Church Universal, which managed to stand out in such a short time among Pentecostals